A Study on Cyanobacteria in Freshwater; with Special Reference to Nanoparticle Synthesis: Exploring the Biochemical and Biological Effects of Cyanobacteria-Mediated Nanoparticle Synthesis (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Metallic nanoparticles synthesis by cyanobacteria presents sequential logical outcomes on a standout amongst the most unique subject concerning biogenic generation of nanoparticles. After an extremely short and general introduction of nanoparticles and cyanobacteria, with regards to (bio) nanotechnology, an abstract on cyanobacteria use to deliver metallic nanoparticles is displayed, centered on their organic ramifications, preferences and hindrances, just as on future prospects. The methods of synthesis of silver (Ag) nanoparticles by the cyanobacteria Spirulina platensis and Nostoc linckia were contemplated. A complex of biochemical, phantom, and investigative methods was utilized to describe biomass and to survey changes in the principle segments of biomass (proteins, lipids, sugars, and phycobilin) during nanoparticle arrangement. The size and state of Ag nanoparticles in the biomass of the two kinds of cyanobacteria were resolved. Neutron initiation examination was utilized to contemplate the gathering elements of the Ag amount. The expository outcomes recommend that the significant decrease of Ag fixation in arrangements and the expansion in biomass happen inside the initial 24 h of investigations. While in this time interim minor changes in the N. linckiaand S. platensis biomass occurred, a critical decrease of the dimensions of proteins, sugars, and phycobiliproteins in the two societies and of lipids in S. platensis was seen after 48 h. In the meantime, the antiradical action of the biomass diminished.